If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9x + -5)(9x + -5) = 0 Reorder the terms: (-5 + 9x)(9x + -5) = 0 Reorder the terms: (-5 + 9x)(-5 + 9x) = 0 Multiply (-5 + 9x) * (-5 + 9x) (-5(-5 + 9x) + 9x * (-5 + 9x)) = 0 ((-5 * -5 + 9x * -5) + 9x * (-5 + 9x)) = 0 ((25 + -45x) + 9x * (-5 + 9x)) = 0 (25 + -45x + (-5 * 9x + 9x * 9x)) = 0 (25 + -45x + (-45x + 81x2)) = 0 Combine like terms: -45x + -45x = -90x (25 + -90x + 81x2) = 0 Solving 25 + -90x + 81x2 = 0 Solving for variable 'x'. Factor a trinomial. (5 + -9x)(5 + -9x) = 0Subproblem 1
Set the factor '(5 + -9x)' equal to zero and attempt to solve: Simplifying 5 + -9x = 0 Solving 5 + -9x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -9x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -9x = 0 + -5 -9x = 0 + -5 Combine like terms: 0 + -5 = -5 -9x = -5 Divide each side by '-9'. x = 0.5555555556 Simplifying x = 0.5555555556Subproblem 2
Set the factor '(5 + -9x)' equal to zero and attempt to solve: Simplifying 5 + -9x = 0 Solving 5 + -9x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -9x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -9x = 0 + -5 -9x = 0 + -5 Combine like terms: 0 + -5 = -5 -9x = -5 Divide each side by '-9'. x = 0.5555555556 Simplifying x = 0.5555555556Solution
x = {0.5555555556, 0.5555555556}
| 7a^3-3a^2+4a+9= | | (-6x+5)+(-4x^2+6x+3)= | | (x-2-3i)(x-2+3i)(x+1)(x-2)=0 | | 2x^225= | | whyunot=work | | 40=110-30t | | 8x+2h=19 | | dropthe=base | | d=110-30t | | this=stupid | | this=dumb | | 3y+2x=-11 | | you=dumb | | 6n^2+24n-18= | | ln=e | | 3*3+34=4 | | n^3+12n^2-23n-10=0 | | 2x+7=6x+49 | | 50x^2=50 | | Y+e=93 | | e(x)-4e(-x)=-3 | | 15+9x=-3+x | | 180-4x-y+10=3x | | 9x+8=15+2 | | 35+3x-11=24 | | 7x-14+4x+29=180 | | 5a+1=6a | | 3(5+3x)=x-3 | | 4y-x+10=3y | | 7x+3y-4x-8y= | | 9x-11=5x+3+18 | | 4x-y+10=3x |